Do fund flows moderate persistence? Evidence from a global study - Miguel, A. (2021)
We investigate whether fund flows eliminate future abnormal performance and persistence as in Berk and Green (2004) using a sample of open-end domestic equity mutual funds from 32 countries. We show that flows have only a small moderating effect on persistence even in the United States, where fund industry conditions most closely resemble the Berk and Green assumptions. In fact, we find that most countries do not have decreasing returns to scale in fund management and, as a result, flows have limited impact on mutual fund performance persistence.